2007
DOI: 10.1111/j.1464-410x.2007.06846.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized prospective trial evaluating testosterone, haemoglobin kinetics and quality of life, during and after 12 months of androgen deprivation after prostatectomy: results from the Postoperative Adjuvant Androgen Deprivation trial

Abstract: OBJECTIVE To assess testosterone and haemoglobin kinetics in the Postoperative Adjuvant Androgen Deprivation (PAAD) trial, and correlate these with quality of life (QoL) in this prospective randomized study. PATIENTS AND METHODS Forty‐three patients met the criteria for high‐risk cancer after RRP (Gleason score ≥ 8, pT3c or Gleason score 7 concomitant with pT3a/b and positive surgical margins) and were prospectively randomized to either observation or AD for 12 months. Haemoglobin and testosterone levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…11 Black et al likewise found that in patients receiving RP adjuvant ADT resulted in only a transient worsening of sexual function. 10 Thus, when ADT is given as adjunctive therapy to BT or EBRT, there is a transient decrease in sexual function that appears to be short-lived. However, in patients with baseline high sexual function scores undergoing RP or BT the HRQOL effects of ADT may be more pronounced and prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…11 Black et al likewise found that in patients receiving RP adjuvant ADT resulted in only a transient worsening of sexual function. 10 Thus, when ADT is given as adjunctive therapy to BT or EBRT, there is a transient decrease in sexual function that appears to be short-lived. However, in patients with baseline high sexual function scores undergoing RP or BT the HRQOL effects of ADT may be more pronounced and prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…Trial participants were at high risk for cancer recurrence based on tumor stage, Gleason score, and surgical margin status [6]. This risk was consistent with a projected 5-year disease free survival rate of approximately 65% or less [1517].…”
Section: Methodsmentioning
confidence: 82%
“…After completing radical retropubic prostatectomy at MD Anderson Cancer Center, men at high risk for recurrence were invited to participate in the Postoperative Adjuvant Androgen Deprivation Trial testing 5-year clinical outcomes in men receiving 1 year of androgen deprivation versus observation [6]. Married men in this trial and their spouses were invited to enroll in a companion study to examine quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations